Assessment of safety for the hermetic closure of an alcoholic drink according to the current regulations - Rodríguez Morales, Adriana
The present article identifies and analyzes the main factors that must be considered while analyzing the safety of the plastic material used in the manufacture of lids, supplied by the suppliers of the capsule of the Liquor Industry of Caldas (ILC, for its initials in Spanish). Additionally, the analysis protocol is established, complying with the regulatory requirements and the technical file on sanitary requirements to be met by materials, articles, containers and plastic equipment intended to come into contact with the beverage for human consumption in order to be applied in the evaluation from providers. The physical, chemical and biological safety risks of glass / plastic closures were assessed through the Failure Mode and Effects Analysis (AMFE, for its initials in Spanish). As established by FAO in the Guide to the Application of Risk Analysis Principles and Procedures, and according to the determination of the critical control points, analysis were carried out in certified laboratories to the suppliers proposed by the industry (codified with letters). Satisfactory results were obtained for chemical risks, such as the maximum limit of heavy metals for all samples. Concerning physical risks, tightening torque, compressive strength and tightness were evaluated, identifying that it complies with the standards established in the industry data sheet. For the analysis of the presence of Leptospira spp, per the reference methods used PCR 16srrs, tested positive, involving biological risk in 1 of the 3-analyzed sample of the B code; migration of pigments into one of the B code samples, total migration below the 8 mg / dm² standard for all samples. With the above, it was established that there is migration of compounds that need to be evaluated by manufacturer B, and improved storage conditions to prevent the proliferation of microorganisms and toxins that affect consumer health